Uncivilised genes human evolution and the urban paradox - Milne, Gustav (Independent Thinking Press, 2017)
In Uncivilised Genes: Human Evolution and the Urban Paradox, Gustav Milne explores how we can reconfigure our lifestyles and urban environments, based on an understanding of our prehistoric past, in order to bring about a richer future for mankind.